A DECISION SUPPORT SYSTEM USING ANALYTICAL HIERARCHY PROCESS (AHP) FOR THE OPTIMAL ENVIRONMENTAL RECLAMATION OF AN OPEN-PIT MINE - Bascetin A. (My University, 2007)
The selection of an optimal reclamation method is one of the most important factors in open-pit design and production planning. It also affects economic considerations in open-pit design as a function of plan location and depth. Furthermore, the selection is a complex multi-person, multi-criteria decision problem. The group decision-making process can be improved by applying a systematic and logical approach to assess the priorities based on the inputs of several specialists from different functional areas within the mine company. The analytical hierarchy process (AHP) can be very useful in involving several decision makers with different conflicting objectives to arrive at a consensus decision. In this paper, the selection of an optimal reclamation method using an AHP-based model was evaluated for coal production in an open-pit coal mine located at Seyitomer region in Turkey. The use of the proposed model indicates that it can be applied to improve the group decision making in selecting a reclamation method that satisfies optimal specifications. Also, it is found that the decision process is systematic and using the proposed model can reduce the time taken to select a optimal method.
Keywords: OPEN-PIT MINING; RECLAMATION METHODS; DECISION MAKING; ANALYTIC HIERARCHY PROCESS